Bernardino Machado e o Ensino Experimental das Ciências - Leonardo, António José F.; Martins, Décio R.; Fiolhais, Carlos (Revista Portuguesa de Pedagogia, 2011)
We analyze the introduction of the Individual Educational Works in the complementary course of Sciences of Secondary Education, an initiative undertaken in 1914 by a government ruled by Bernardino Machado. The impact of one of the first republican reforms on this level of education is evaluated based on the study conducted in 1918 by the Spanish Rubén Landa on the Portuguese secondary education system, which focused on the Pedro Nunes high school, in Lisbon, considered to be the best in Portugal in that period. The implementation of practical work to complement the disciplines of Physics, Chemistry, Natural Sciences and Geography culminated of a process initiated with the reform of 1905, whose programs of the scientific disciplines, in the general course, included innovative pedagogical recommendations, highlighting the relevance of experimental work.